LEVE I BYEN ELLER MED BYEN - BY OG LITTERATUR EFTER MODERNISMEN - Larsen, Svend Erik (K&K - Kultur og Klasse, 2010)
LIVING IN THE CITY OR LIVING WITH THE CITY. CITY AND LITERATURE AFTER MODERNISM Since the mid-18th century literature has been increasingly preoccupied with the city as the locus of modernity. Here everything that characterised modernity as a broad cultural and social development was assembled in the most concentrated and visible form, including the contradictions and ambiguities of modernity. The more that cities developed in size, function and layout during the 19th and early 20th centuries on both a European and a global scale, the more detailed and ambiguous their effect became on literature and the other arts in the emerging new and changing old media, now gathered under the heterogeneous umbrella of modernism. The emergent field of sociology gave the city its theoretical and philosophical meta-reflection from around 1900. However, the modernist movement also locked the conception of the city in its own conceptualisation and representation, impeded a fresh view of the city of today on a global scale, and barred the way to an alternative view of previous urban history. This paper tries to open a door leading to the reconceptualisation of the city in relation to the study of literature by emphasising the notion of network and by analysing works by Jess Ørnsbo and Amitav Ghosh with brief reference to Jens Baggesen, Jon Dos Passos and Jens Smærup Sørensen.